Power of Homomorphic Encryption in Secure Data Processing - Muhammad Asif Ibrahim; Syed Khuram Hassan (International Journal for Electronic Crime Investigation, 2024)
Homomorphic encryption is a form of encryption that allows computations to be performed on encrypted data without first having to decrypt it. This paper presents a detailed discussion of HE, a critical component in the protection of data in today’s technology-driven environment. First, homomorphic encryption and its terminology will be introduced and then development process from the beginning to the present state will be discussed. Different classes of homomorphic encryption and analysis of internal workings and architecture of homomorphic encryption will be discussed. The usefulness of this technology in ensuring privacy in sensitive areas is discussed, as well as the limitations that may hinder the technology’s advancement, including computation intensity and data growth. The paper also reasserts the massive application of homomorphic encryption in data security and privacy, stressing the need to continue the advancement to overcome existing drawbacks and enhance the application of the technique. While moving vast distances within the digital arena, the optimization of homomorphic encryption remains the guiding light to our freedom and privacy online.